The Fall of the Alberto Fujimori Government: New Evidence and Interpretations. (September 2019) - Santander Joo, Carlos Ugo; Domínguez Avila, Carlos Federico
New evidence and interpretations regarding the end of the authoritarian Alberto Fujimori regime and the Peruvian democratic transition of 2000 suggest that preexisting electoral and institutional rules intrinsic to the authoritarian regime contributed to a process of regime change. Thus Peru can be seen as one of the few Latin American nations in which the transition was caused by a rupture in contrast to the pacted-reform/rupture transitions most common in the region. Nuevas evidencias e interpretaciones sobre el fin del régimen autoritario de Alberto Fujimori y la transición democrática en 2000 sugieren que las elecciones y las reglas institucionales preexistentes y propias de la naturaleza de un régimen autoritario contribuyeron a un proceso de cambio de régimen. Así, Perú puede ser considerado entre los pocos países en el concierto latinoamericano en los que se estableció una transición por ruptura a diferencia de las transiciones por pactada-reforma/ruptura predominante en la region.